Plasma cell myeloma – therapeutic opportunities - Orzechowska, Aleksandra; Widłak, Karolina; Pawłowski, Piotr; Ziętara, Karolina; Orzechowska, Julia (Journal of Education, Health and Sport, 2022)
Introduction: Plasmocytic myeloma (PCM) is a neoplastic disease with a multistage course. Monoclonal plasmocytes undergo uncontrolled, multifocal growth in the bone marrow, which results in the production of monoclonal immunoglobulin or its fragments that damage the bone marrow. Aim: The aim of this study is to present selected therapeutic possibilities of multiple myeloma. Materials and methods: The work uses the method of non-systematic review and analysis of the available scientific literature. Databases such as PubMed, Google Scholar, Arianta, Scopus, Web of Science were searched. The years 2005-2022 were assumed as the review period. Discussion: Multiple myeloma accounts for 1-2% of all cancer cases, and 10-15% of all hematological cancers. It is the third most common lymphoid neoplasm after chronic lymphocytic leukemia and large B-cell lymphoma. The diagnosis of PCM requires the presence of a minimum of 10% clonal plasmocytes in the bone marrow or biopsy confirmed plasmocytoma. Moreover, the CRAB and SLiM CRAB criteria are also important. Treatment should be initiated in all symptomatic patients meeting the SLiM CRAB criteria. The first stage of treatment is to induce remission of the disease. Conclusions: Thanks to the progress of medicine, an increasing percentage of patients achieve permanent remissions. The success of the therapy is a component of the earliest possible detection of the disease and the use of appropriate, individually selected drugs.